The salt merchants of Tianjin : state-making and civil society in late Imperial China - Kwan, Man Bun, 1955- (University of Hawai'i Press, 2001)
Modernity, moreover, was not kind to this local articulation of Chinese "civil society." While the city endured the ravages of civil war and foreign invasions in the late Qing, both officials and intellectuals advocated the reassertion of state authority to re-create a strong and corporatist state capable of revitalizing the country. The forced bankruptcy of several leading salt merchants and the re-nationalization of their monopolies in 1911 signaled a fundamental shift in state-society relations, abrogating in the process centuries of "useful compromises" that had once integrated the two."--Jacket